The bread making process of ancient wheat: A semi-structured interview to bakers. (May 2019) - Guerrini, Lorenzo; Parenti, Ottavia; Angeloni, Giulia; Zanoni, Bruno
Abstract: The importance of bread made from ancient wheat flours is currently increasing. In literature, several works examine the cultivation phase of ancient wheats, as well as their positive effects on human health. On a technological level, their bread-making process is hindered by the poor workability of these flours, but there are only few scientific studies aimed to enhance their technological performance. However, bakers developed several strategies to improve ancient wheat flour processability. We chose the semi-structured interview as instrument to investigate these strategies, evaluating them according to the existent literature. The study revealed that ancient wheats are usually stone milled, and processed as brown flours. Bread doughs are often prepared with flour blends, resulting from the cultivation of grain mixtures or obtained as flour mix. The choice of slow mixers, an accurate monitoring of the final leavening phase and the use of sourdough, as well as the selection of flour blends have been proposed as solutions to partially improve the technological performance of ancient wheat flours. Finally, ancient wheat varieties are usually processed following several "good working practices" (i.e. use of non-refined flours, sourdough, organic cultivations) which probably play a role in enhancing their beneficial effects on human health. Highlights: Ancient wheat flours are typically characterized by poor technological properties. Ancient wheats are generally stone-milled and processed as brown flours. Doughs are prepared with flour blends from mixed cultivations or flour mixtures. Slow mixers and high viability sourdough improve flours' processability. Monitoring the leavening step and bake in a temperature drop increase bread quality.